1994
DOI: 10.1093/ajcn/59.6.1362
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal effects and energy value of polydextrose in healthy nonobese men

Abstract: We studied seven healthy volunteers before and during acute (PD1) and chronic (PD2) ingestion of 30 g polydextrose (PD)/d. The energy value of PD was assessed after [U-14C]PD was added to the 10-g morning dose of PD during PD1 and at the end of PD2. Thirty-one +/- five percent (mean +/- SD) (PD1) and 29 +/- 4% (PD2) of the dose appeared in breath within 48 h. A small fraction of the ingested radioactivity was recovered in urine (4 +/- 1%) and excreted in flatus (< or = 1%) and in feces as volatile fatty acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 17 publications
3
41
0
5
Order By: Relevance
“…could be because the intestinal environment was improved by PDX, which induces an increase in fecal bulk, softens stools, lowers fecal pH, and is partially fermented in the large bowel (8)(9)(10)(11), and which was also shown to be selectively fermented by the fecal microbiota and to have stimulated bifidobacterial growth in an in vitro study (28).…”
Section: Discussionmentioning
confidence: 99%
“…could be because the intestinal environment was improved by PDX, which induces an increase in fecal bulk, softens stools, lowers fecal pH, and is partially fermented in the large bowel (8)(9)(10)(11), and which was also shown to be selectively fermented by the fecal microbiota and to have stimulated bifidobacterial growth in an in vitro study (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the nature of the glycosidic bonds in polydextrose renders it only partially fermented by intestinal microorganisms and resistant to enzymatic attack (1,6). It is a water-soluble, randomly bonded, condensation polymer of glucose containing small amounts of sorbitol and citric acid (24).…”
mentioning
confidence: 99%
“…The effect of "acute" polydextrose ingestion (days 9-16, 30 g/day) and "chronic" polydextrose ingestion (days 17-38, 30 g/day) compared to the "control" period without polydextrose consumption (days 1-8, 0 g/day) on gastro-intestinal transit time and faecal weight was evaluated by Achour et al (1994) in a non-randomised sequential study in seven male volunteers on a controlled diet. The Panel considers that no conclusions can be drawn from this uncontrolled study for the scientific substantiation of the claim.…”
Section: Changes In Bowel Function (Id 784)mentioning
confidence: 99%